THE “WHAT’S UP?” SURVEY OF ADOLESCENTS IN RESIDENTIAL CARE FACILITIES DURING THE ISRAEL–HAMAS WAR - Alfasi, Ben; Reznikovski-Kuras, Anna; Arazi, Tal (International Journal of Child, Youth and Family Studies, 2025)
On October 7, 2023, the Hamas organization launched a surprise terrorist attack, to which Israel responded by declaring war on Hamas. The aim of this study was to examine the status and needs of adolescents in residential care facilities (RCFs) throughout Israel in light of the ongoing war. An additional aim was to show that our survey itself conveyed the message to the adolescents that the professionals and administrative staff of the RCFs are concerned about them. The study relied on a quantitative research approach, using a self-report online survey among adolescents in RCFs; 340 questionnaires were collected. The adolescents reported emotional needs that surfaced because of the war: 58% felt sad or depressed, 50% were worried or stressed, and 49% were angry or irritable. However, 62% reported feeling safe in their RCF. A multivariate linear regression analysis revealed that a feeling on the part of the adolescents that (a) the RCF staff care about their well-being and (b) they listen to and support them are predictors of the adolescents’ sense of security in the RCF. The findings suggest that developing policies aimed at strengthening the connection between RCF staff and the adolescents in their care, and enhancing strategies of partnership, are essential for increasing the adolescents’ sense of security.